Galleria mellonella Reveals Niche Differences Between Highly Pathogenic and Closely Related Strains of Francisella spp. - Thelaus, Johanna; Lundmark, Eva; Lindgren, Petter; Sjödin, Andreas; Forsman, Mats (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis, a highly virulent bacteria that causes the zoonotic disease tularemia, is considered a potential agent of biological warfare and bioterrorism. Although the host range for several species within the Francisella is known, little is known about the natural reservoirs of various Francisella species. The lack of knowledge regarding the environmental fates of these pathogens greatly reduces the possibilities for microbial risk assessments. The greater wax moth (Galleria mellonella) is an insect of the order Lepidoptera that has been used as an alternative model to study microbial infection during recent years. The aim of this study was to evaluate G. mellonella as a model system for studies of human pathogenic and closely related opportunistic and non-pathogenic strains within the Francisella genus. The employed G. mellonella larvae model demonstrated differences in lethality between human pathogenic and human non-pathogenic or opportunistic Francisella species. The F. novicida, F. hispaniensis and F. philomiragia strains were significantly more lethal in the G. mellonella model than the strains of human pathogens F. t. holarctica and F. t. tularensis. Our data show that G. mellonella is a possible in vivo model of insect immunity for studies of both opportunistic and virulent lineages of Francisella spp., that produces inverse results regarding lethality in G. mellonella and incapacitating disease in humans. The results provide insight into the potential host specificity of F. tularensis and closely related members of the same genus, thus increasing our present understanding of Francisella spp. ecology.